Cutaneous C-Fiber Pain Abnormalities of Fibromyalgia Patients are Specifically Related to Temporal Summation - Staud, Roland (2008)
Temporal summation of “second pain” (TSSP) is considered to be the result of C-fiber-evoked responses of dorsal horn neurons, termed ‘windup’. TSSP is dependent on stimulus frequency (≥ 0.33 Hz) and relevant for central sensitization and chronic pain. We have previously shown that compared to normal controls (NC), fibromyalgia (FM) subjects show abnormal TSSP, requiring lower stimulus intensities/frequencies to achieve similar TSSP. However, it is unknown whether abnormal TSSP in FM is influenced by peripheral sensitization of C-fiber nociceptors and/or bias in pain ratings. Thus we evaluated 14 FM subjects and 19 NC with pain threshold tests to selective C-fiber stimulation, 30 sec heat stimuli, and repetitive brief (1.5 sec) heat pulses at 0.33 Hz using a contact heat stimulator (CHEPS). The intensity of heat pulses was varied to achieve maximal TSSP ratings of 45 ± 10 (numerical pain scale 0–100) in both FM and NC groups. We found that NC and FM subjects had similar pain thresholds to C-fiber stimulation and yet FM subjects required lower heat pulse temperatures to generate the same magnitudes of TSSP (p < .05). This combination of findings does not support peripheral sensitization and suggests central TSSP abnormalities in FM subjects. In a second experiment, all aspects of individually adjusted TSSP heat pulses were kept the same except the baseline temperature (BT) between heat pulses was surreptitiously alternated between 35°C and 40°C. These changes of BT resulted in significantly greater TSSP ratings of FM subjects compared to NC subjects, both at 35°C or 40°C, but did not change their response to the first heat pulse of a stimulus train. These findings provide strong support for alterations of central pain sensitivity and not peripheral sensitization or rating bias as responsible for TSSP differences between NC and FM subjects.